E-Marketplace Strategies to Drive Popularity, Virality, and Engagement on Twitter - Thongmak, Mathupayas (International Journal of Electronic Commerce Studies, 2025)
Purpose – The purpose of this study is to investigate e-marketplace strategies to drive popularity, virality, and engagement on Twitter and the moderating impact of e-marketplaces. Design/methodology/approach – Twitter data from two e-marketplaces posted within 6 months were collected. Content strategies in terms of length, interactivity, novelty, consistency, content features, media strategies in terms of vividness features, and scheduling strategies in terms of timing features were extracted using Twitter data mining tools, an intent mining tool, a Generative AI, and a spreadsheet. Hierarchical regressions were applied to investigate relationships between these strategies and customer engagement. Findings – Length, interactivity (having URLs), novelty (price, place, promotion, physical evidence information), content (message intent: sentiment), vividness (media type: texts and photos) decrease popularity/ virality/ engagement, while interactivity (hashtags and mentions), novelty (people), consistency (brand mentioned), vividness (having media URLs), timing (Mon-Fri, except Thu) increase them. E-marketplace brands are also significant moderators. Practical implications – This work reflects e-marketplace strategies each brand employs, guides them to adjust their content, media, and scheduling strategies to gain more likes and retweets, and reveals the impact of their brands as a moderator. Originality/value – Using novel techniques to collect and process data and introducing unique content themes (7Ps) to investigate firm-generated content in the e-marketplace context expands the knowledge in social media marketing literature.